FUEL PLANNING PROBLEMS FOR FLIGHTS, PLANNED VIA STANDARD ARRIVAL ROUTES (STAR) WITH DELAY LEGS - V. G. Lugovoi; A. V. Sorokin; O. V. Shilov (Научный вестник МГТУ ГА, 2019)
The article deals with the fuel planning problems for flights planned via standard arrival routes (STAR), with delay legs. Implementation of new standard arrival routes based on area navigation principles leads to increasing airspace capacity and reducing workload for both flight crews and air traffic controllers. More and more air navigation service providers implement modern STARs which include delay legs as their components. Delay legs are being used as modern alternative to delay actions performed with short time holding patterns or radar vectoring procedures. But, new STAR types’ implementation without changing fuel planning procedures has led to fuel consumption increase. The nature of problem is shown in the article with reference to recently designed, published and implemented Pulkovo airport new standard arrival routes with delay legs. The calculations made with the use of automated flight planning systems and shown extra fuel consumption are given. Contributing negative factors are described. Suggested methods of solving the problems allow avoiding extra fuel consumption and reducing pollution. The procedure for using the new approach to planning and performing flight via STARs with delay legs is described. Implementation of the new approach in arrival trajectory design, flight planning and flight performance via standard arrival routes with delay legs is actual for the existing arrival routes and the routes being projected.